Nanotribology and nanomechanics II Nanotribology, biomimetics, and industrial applications - Bhushan, Bharat 1949-.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
The comprehensive reference and textbook serves as a timely, practical introduction to the principles of nanotribology and. Assuming some familiarity with macroscopic tribology, the book comprises chapters by internationally recognized experts, who integrate knowledge of the field from the mechanics and materials-science perspectives. They cover key measurement techniques, their applications, and theoretical modelling of interfaces, each beginning their contributions with macro- and progressing to microconcepts.
Nanotribology, Nanomechanics, and Materials Characterization -- Surface Forces and Nanorheology of Molecularly Thin Films -- Interfacial Forces and Spectroscopic of Confined Fluids -- Friction and Wear on the Atomic Scale -- Mechanical Properties of Nanostructures -- Scale Effect in Mechanical Properties and Tribology -- Nanotribology of Ultrathin and Hard Amorphous Carbon Films -- Self-Assembled Monolayers for Nanotribology and Surface Protection -- Nanoscale Boundary Lubrication Studies -- Lotus Effect: Roughness-Induced Superhydrophobic Surfaces -- Gecko Feet -- Micro/Nanotribology and Micro/Nanomechanics of Magnetic Storage Devices -- MEMS/NEMS and BioMEMS/NEMS: Materials and Devices and Biomimetics -- Mechanical Properties of Micromachined Structures -- Structural, Nanomechanical and Nanotribological Characterization of Human Hair Using Atomic Force Microscopy and Nanoindentation.
Electronic reproduction.
Keywords: Tribology; Nanotechnology; Electronic books